2001
DOI: 10.1073/pnas.181344198
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β-major globin gene transcription is associated with recruitment of NF-E2 to the β-globin LCR and gene promoter

Abstract: The mouse ␤-globin gene locus control region (LCR), located upstream of the ␤-globin gene cluster, is essential for the activated transcription of genes in the cluster. The LCR contains multiple binding sites for transactivators, including Maf-recognition elements (MAREs). However, little is known about the specific proteins that bind to these sites or the time at which they bind during erythroid differentiation. We have performed chromatin immunoprecipitation experiments to determine the recruitment of the er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
158
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(173 citation statements)
references
References 48 publications
(48 reference statements)
14
158
0
1
Order By: Relevance
“…Immunoprecipitated DNA was analyzed by PCR using primers specific for the human p53 gene promoter. For the semi-quantitative ChIP assay, duplex-PCR was performed as described (Sawado et al, 2001). Primer sequences used for ChIP assays are available by request.…”
Section: Chip Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoprecipitated DNA was analyzed by PCR using primers specific for the human p53 gene promoter. For the semi-quantitative ChIP assay, duplex-PCR was performed as described (Sawado et al, 2001). Primer sequences used for ChIP assays are available by request.…”
Section: Chip Assaymentioning
confidence: 99%
“…Primer sequences used for ChIP assays are available by request. For the duplex PCR we used for normalization b-actin for the close histone marks and MyoD for open histone marks (Sawado et al, 2001). For each antibody, at least three independent ChIP experiments were performed.…”
Section: Chip Assaymentioning
confidence: 99%
“…p45 NF-E2, which contains a transactivation domain, interacts with TAFII130 (Amrolia et al 1997) and CBP in vitro (Cheng et al 1997;Hung et al 2001) and is required for pol II recruitment to the ␤ maj globin gene promoter in mouse erythroleukemia (MEL) cells (Johnson et al 2001). Recently, we reported that NF-E2 binds to both the LCR and the ␤-globin promoter region, even though no canonical NF-E2 binding sites are present in the promoter (Sawado et al 2001). This observation has reinforced speculation that the LCR functions through interactions with the promoter.…”
mentioning
confidence: 99%
“…To gain insight into which transcription events are influenced by the LCR, we have performed ChIP analyses of histone modifications and factor recruitment at the adult ␤-globin gene in two model systems: (1) differentiation of 745A MEL cells, a process accompanied by a greater than 100-fold increase in ␤-globin gene expression (Sawado et al 2001); and (2) primary erythroid cells derived from ⌬LCR/WT heterozygous mice.…”
mentioning
confidence: 99%
“…However, in uninduced MEL cells, it is maintained at the basal level but the locus is still kept open without detectable change from the state of induced cells. (33,34) After opening the domain, the distal enhancer elements further augment transcription. Hence, the strandbreaking model does not exclude the looping or linking model.…”
Section: Chromatin Remodeling and Chromatin Domain Openingmentioning
confidence: 99%